Comparative Analysis of Cartoon Communication on Panama Leaks in Elite Pakistani Press - Sarwar, Dr. muhammad Haseeb (Journal of Peace, Development and Communication, 2021)
Cartoon communication is a powerful tool to make real comments in a humorous way. Socio-political cartoons convey sensitive content and have been particularly practiced in Pakistan from the era of black laws when media and press had no freedom of speech. So, political cartoon communication has been an efficient technique to convey withhold information and criticize the tycoons. Panama leaks were 11.5 million internal documents publicly presented by The International Consortium of Investigative Journalists (ICIJ) against the corrupt officials, in which the then sitting prime minister of Pakistan was also involved. In this paper, we collected a new dataset of cartoons on panama leaks published in two English newspapers Daily Dawn and Daily Nation, from April 2016 to July 2017 based upon four categories: 1) change in Pakistani politics, 2) Effect on economy, 3) corruption in elite class, and 4) impacts on international relations. To get more insights from panama visuals we have categorized our data into favorable, unfavorable and neutral cartoons. Based upon these categories of construction, five different research hypotheses are built and z-test is conducted to collected statistical results. Our results show that both newspapers have published a rich amount of cartoons on panama leaks as Daily Dawn printed 68% national and 32% international cartoons, while Daily Nation printed 72% national and 28% international cartoons. Our study concludes that Daily dawn published 24% favorable, 59% unfavorable and 17% neutral cartoons while Daily Nation issued 31% favorable, 59% unfavorable and 10% neutral cartoons.